Microstructured Photo‐Crosslinked Poly(Trimethylene Carbonate) for Use in Soft Lithography Applications: A Biodegradable Alternative for Poly(Dimethylsiloxane). Issue 16 (28th February 2018) - Schüller‐Ravoo, Sigrid; Teixeira, Sandra M.; Papenburg, Bernke; Stamatialis, Dimitrios; Feijen, Jan; Grijpma, Dirk W.
Abstract: Photo‐crosslinkable poly(trimethylene carbonate) (PTMC) macromers were used to fabricate microstructured surfaces. Microstructured PTMC surfaces were obtained by hot embossing the macromer against structured silicon masters and subsequent photo‐crosslinking, resulting in network formation. The microstructures of the master could be precisely replicated, limiting the shrinkage. Microstructured PTMC was investigated for use in two different applications: as stamping material to transfer a model protein to another surface and as structured substrate for cell culture. Using the flexible and elastic materials as stamps, bovine serum albumin labelled with fluorescein isothiocyanate was patterned on glass surfaces. In cell culture experiments, the behavior of human mesenchymal stem cells on nonstructured and microstructured PTMC surfaces was investigated. The cells strongly adhered to the PTMC surfaces and proliferated well. Compared to poly(dimethylsiloxane) (PDMS), which is commonly used in soft lithography, the PTMC networks offer significant advantages. They show better compatibility with cells, are biodegradable, and have much better mechanical properties. Both materials are transparent, flexible, and elastic at room temperature, but the tear resistance of PTMC networks is much higher than that of PDMS. Thus, PTMC might be an alternative material to PDMS in the fields of biology, medicine, and tissue engineering, in which microfabricated devices are increasingly being applied. Abstract : Move over PDMS : Photo‐crosslinkable poly(trimethylene carbonate) (PTMC) macromers are used to fabricate microstructured surfaces for use in two different applications: as stamping material to transfer a model protein to another surface and as structured substrate for cell culture. Compared to poly(dimethylsiloxane) (PDMS), which is commonly used in soft lithography, the PTMC networks offer significant advantages.